Enhanced Conversion Efficiency of Monocrystalline P‐Type Passivated Emitter and Rear Cells in Commercial Production Line by Improving Rear Side Passivation. Issue 7 (18th May 2021) - Pu, Tian; Shen, Honglie; Hong Neoh, Kuang; Ye, Fei; Tang, Quntao
Abstract : An industrially proven method for increasing cell efficiency of monocrystalline P‐type PERC cells is reported, whereby a layer of silicon oxide or silicon oxynitride (SiO x /SiO x N y ) is sandwiched between aluminum oxide (AlO x ) and silicon nitride (SiN x ) in the rear passivation stack, forming an AlO x  + SiO x /SiO x N y  + SiN x structure. This additional layer will theoretically improve the rear side optical and electrical properties for the cell. By adjusting the flow ratio of N2 O:NH3, SiO x /SiO x N y with different refractive indices were fabricated. Optimization of the SiO x film thickness showed a 0.11% efficiency gain in monofacial P‐type PERC cells because of higher short‐circuit current ( I sc ) and fill factor (FF), whereas optimization of the SiO x N y film refractive index showed a 0.05% efficiency gain in bifacial P‐type PERC cells due to the improvement of I sc and FF too. The current gain is believed to be benefited from the optimized light‐absorbing performance of the composite passivation layer structure. Furthermore, it is demonstrated that the refractive index of the SiN x capping layer had to be tuned after the incorporation of SiO x /SiO x N y to improve the cell efficiency. Abstract : A novel SiO x or SiO x N y layer is sandwiched between AlO x and SiN x in the rear passivation stack to improve the rear side optical and electrical properties for the monofacial (efficiency gain over 0.1% mainly comes from current and fill factor) and bifacial (efficiency gain over 0.05% mainly comes from current) P‐PERC solar cell.